Driving Performance after Bedtime Administration of Daridorexant, Assessed in a Sensitive Simulator - Muehlan, Clemens; Brooks, Sander; Vaillant, Cedric; Meinel, Michael; Jacobs, Gabriël E.; Zuiker, Rob G.; Dingemanse, Jasper (Clinical pharmacology and therapeutics, 2022)
Use of hypnotics is often associated with next‐morning residual effects and a higher risk of motor vehicle accidents. Measuring next‐morning effects on driving performance is therefore advised by regulatory agencies. Here, we examined driving performance following administration of daridorexant, a new dual orexin receptor antagonist developed to treat insomnia. Sixty healthy male and female subjects (50–79 years of age) were randomized in a placebo‐ and active‐controlled, four‐way cross‐over study. Each subject received evening administration of daridorexant 50 and 100 mg, zopiclone 7.5 mg, and placebo, in separate treatment phases of 4 days. Simulated driving performance was assessed after initial (day 2) and repeated dosing (day 5), 9 hours postdose. Standard deviation of the lateral position (SDLP) was the main outcome. On both days, with zopiclone, SDLP increased significantly compared with placebo, which confirmed sensitivity of the simulator. With daridorexant, on day 2, the placebo‐corrected mean (97.5% confidence interval) SDLP increased by 2.19 cm (0.46–3.93) and 4.43 cm (2.72–6.15) for 50 and 100 mg, respectively. On day 5, SDLP values for both daridorexant doses were significantly below the prespecified threshold of impairment (2.6 cm) and statistically not different from placebo. Daridorexant showed a lower self‐rated driving quality and higher effort compared to placebo on day 2 but not on day 5. In non‐insomnia subjects, daridorexant impaired simulated driving after initial but not after repeated dosing. Subjects should be cautioned about driving until they know how daridorexant affects them.